METHODS OF FORMATION OF LOGICAL COMPETENCE IN STUDENTS (Scientific journal of the Fergana State University, 2023)
This article talks about methods and methods of solving mathematical problems, pedagogical thinking, developing economic skills and competencies in students in the field of pedagogy in educational processes and in the process of teaching mathematics in general secondary schools. In addition, if attention is paid to the use of economic issues in the formation of theoretical thinking, the student's knowledge, professional training, and the opportunities to educate him as a morally mature person will expand even more.